Bandgap Engineering in Novel Fluorite‐Type Rare Earth High‐Entropy Oxides (RE‐HEOs) with Computational and Experimental Validation for Photocatalytic Water Splitting Applications. (1st May 2022) - Nundy, Srijita; Tatar, Dalibor; Kojčinović, Jelena; Ullah, Habib; Ghosh, Aritra; Mallick, Tapas K.; Meinusch, Rafael; Smarsly, Bernd M.; Tahir, Asif Ali; Djerdj, Igor
Abstract: Five different rare‐earth‐based nanocrystalline high entropy oxides (HEOs) with fluorite structure and average crystallite sizes between 6 and 8 nm are prepared and their photocatalytic behavior toward azo dye degradation and photoelectrochemical water splitting for hydrogen generation is examined. The cationic site in the fluorite lattice consists of five equimolar elements selected from the group of rare‐earth elements including La, Ce, Pr, Eu, and Gd and second‐row transition metals, Y and Zr. The studied HEOs exhibit bandgaps in the range from 1.91 to 3.0 eV and appropriate valence and conduction bands for water splitting. They reveal high photocatalytic activity that is mostly attributed to the accessibility of more photocatalytic active sites, which provide radicals responsible for the azo dye degradation. The materials successfully produce hydrogen by photocatalytic water splitting, suggesting the potential of HEOs as new photocatalysts. The photocatalytic performances of all studied HEOs outperform the single fluorite oxides or equivalent mixed oxides. The Ce0.2 Zr0.2 La0.2 Pr0.2 Y0.2 O2 (CZLPY) engender hydrogen in 9.2 µmol mg −1 per hour that is much higher content than for pristine CeO2 material which amounts to 0.8 µmol mg −1 per hour. Abstract : Five different nanocrystalline rare‐earth‐based high entropy oxides (HEOs) with fluorite crystal structure are synthesized. The studied HEO photocatalysts for azo dye degradation and photochemical water splitting for hydrogen generation outperform the single fluorite oxides or equivalent mixed oxides. The photocatalyst with the best performance (Ce0.2 Zr0.2 La0.2 Pr0.2 Y0.2 O2 ) is additionally investigated by theoretical modelling using density functional theory.